Mengukur pengaruh penting dari bauran pemasaran terhadap kepuasan konsumen - Pascalina, Donna (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The development of the fashion industry is currently experiencing a significant increase in the last decade. The high competition in this industry requires companies to be able to improve their marketing strategies and it is necessary to study how product quality can increase customer satisfaction. This study aims to determine how the marketing mix variables consisting of product, price, place and promotion affect consumer satisfaction on Uniqlo products in the city of Bandung. The sample was selected as many as 200 respondents from Uniqlo visitors in the city of Bandung. This study uses a quantitative approach using the explanatory method by distributing questionnaires. The results of the study prove that the marketing mix variable consisting of product, price, place and promotion has a partial effect on consumer satisfaction. The results of testing the coefficient of determination obtained 66.4% which the results are included in the high category. This shows that the four variables provide a fairly high contribution in explaining consumer satisfaction in the city of Bandung. This research is also expected to contribute to the company, especially in marketing strategies to always maintain product quality and other variables in the marketing mix so that an advantage is obtained for the company.